Alternol, a natural compound, exerts an anti‐tumour effect on osteosarcoma by modulating of STAT3 and ROS/MAPK signalling pathways. Issue 2 (14th September 2016) - Zuo, Dongqing; Zhou, Zifei; Wang, Hongsheng; Zhang, Tao; Zang, Jie; Yin, Fei; Sun, Wei; Chen, Jiepeng; Duan, Lili; Xu, Jing; Wang, Zhuoying; Wang, Chongren; et al.
Abstract: Osteosarcoma (OS) is the most frequent primary malignant bone tumour. Alternol, a novel compound purified from microbial fermentation products exerts anti‐tumour effects across several cancer types. The effect of alternol on human OS remains to be elucidated. We first evaluated the anti‐tumour effect of alternol in several human OS cell lines in vitro and investigated its underlying mechanism. Alternol inhibited OS cell proliferation, migration and induced caspase‐dependent apoptosis, G2/M cell cycle arrest in a dose and time‐dependent manner. Moreover, alternol treatment inhibited signal transducer and activator of transcription‐3 (STAT3) phosphorylation in 143B and MG63 human OS cells, as evaluated using a STAT3‐dependent dual luciferase reporter system. Exposure to alternol resulted in excessive reactive oxygen species (ROS) generation and Jun amino‐terminal kinases (JNK), extracellular signal‐regulated kinases (ERK1/2) and p38 activation. Furthermore, alternol‐induced cell death was significantly restored in the presence of the ROS scavenger, N ‐acetyl‐l ‐cysteine (NAC) or a caspase inhibitor Z‐VAD‐FMK. NAC also prevented G2/M phase arrest and phosphorylation of mitogen‐activated protein kinases (MAPK), but did not reverse STAT3 inactivation. Finally, alternol suppressed tumour growth in vivo in the nude mouse OS tibia orthotopic model. Immunohistochemistry revealed that alternol treatment resulted in down‐regulation of phosph‐STAT3 Tyr705 and up‐regulation of cleaved caspase‐3 and phosph‐SAPK (Stress‐activated protein kinases)/JNK expression. Taken together, our results reveal that alternol suppresses cell proliferation, migration and induces apoptosis, cell cycle arrest by modulating of ROS‐dependent MAPK and STAT3 signalling pathways in human OS cells. Therefore, alternol is a promising candidate for developing anti‐tumour drugs target OS.